Microwave induced fast pyrolysis of scrap rubber tires - Ani, Farid Nasir (American Institute of Physics, 2012)
Pyrolysis is the thermal degradation of carbonaceous solid by heat in the absence of oxygen. The feedstocks, such as biomass or solid wastes are heated to a temperature between 400 and 600°C, without introducing oxygen to support the reaction. The reaction produces three products: gas, pyro-fuel oil and char. This paper presents the techniques of producing pyro-oil from waste tires, as well as investigation of the fuel properties suitable for diesel engine applications. In this study, microwave heating technique is employed to pyrolyse the used rubber tires into pyro-oil. Thermal treatment of as received used rubber tires is carried out in a modified domestic microwave heated fixed bed technology. It has been found that, rubber tires, previously used by various researchers, are poor microwave absorbers. Studies have shown that an appropriate microwave-absorbing material, such as biomass char or activated carbon, could be added to enhance the pyrolysis process; thus producing the pyro-oil. The characteristics of pyro-oil, as well as the effect of microwave absorber on its yield, are briefly described in this paper. The temperature profiles during the microwave heating process are also illustratively emphasized. The study provides a means of converting scrap tires into pyro-oil and pyrolytic carbon black production. The proposed microwave thermal conversion process therefore has the potentials of substantially saving time and energy.